Volume and Transport Properties of Binary Liquid Systems of N,N-Dimethylformamide with Aromatic Ketones at 308.15 K - Jyotsna Tangeda, Savitha; Nallani, Satyanarayana (Asian Journal of Chemistry, 2016)
The densities of binary mixtures of N,N-dimethylformamide with 1-phenyl-ethanone, 1-phenyl-propan-1-one, 1-p-tolyl-ethanone and 1-(4-chloro-phenyl)ethanone have been determined and used to calculate the excess molar volumes. Flow times of the mixtures have also been determined. Using densities and flow times, values of the deviations in viscosity have been calculated. All VE vs. x1 isotherms are sigmoidal whereas all Dh vs. x1 isotherms are not sigmoidal. This trend indicates that both specific and non-specific interactions are operative between unlike molecules of the mixtures.